Cultura tributaria de las microempresas comerciales y su impacto en el desarrollo socio-económico de la Provincia de Manabí, 2017. - Muñoz Anchundia, Verónica Isabel (2018)
The objective of this research was to evaluate the incidence of the tax culture of commercial microenterprises in the socio-economic development of the province of Manabí, 2017, in order to carry out the research, three methodological phases were carried out. variables of the tax culture and socio-economic development, through a bibliographic review and validation of the indicators through the application of the Delphi method, these indicators are: tax collection, perceptions in the tax process and causes of evasion for the primary variable, in relation to the second variable, the indicators are social investment, associated risks and equitable distribution of tax revenues. As a second aspect, the current state of the study variables was determined, applying an ad hoc structured survey with a Likert scale, a sample of the microentrepreneurs, analyzing the results obtained by SPSS. The last phase was the correlation between the variables through the Pearson test, concluding that the tax culture positively influences the socio-economic untiement of the province and that this correlation was 0.9 on the Pearson scale.